The other mothers : [large type] a novel - Faulkner, Katherine (Thorndike Press large print dynamic drama., 2024)
"When a young nanny is found dead in mysterious circumstances, new mom, Tash, is intrigued. She has been searching for a story to launch her career as a freelance journalist. But she has also been searching for something else--new friends to help her navigate motherhood. She sees them at her son's new playgroup. The other mothers. A group of sleek, sophisticated women who live in a neighborhood of tree-lined avenues and stunning houses. The sort of mothers Tash herself would like to be. When the mothers welcome her into their circle, Tash discovers the kind of life she has always dreamt of--their elegant London townhouses a far cry from her cramped basement flat and endless bills. She is quickly swept up into their wealthy world via coffees, cocktails, and playdates. But when another young woman is found dead, it's clear there's much more to the community than meets the eye. The more Tash investigates, the more she's led uncomfortably close to the other mothers. Are these women really her friends? Or is there another, more dangerous reason why she has been so quickly accepted into their exclusive world? Who, exactly, is investigating who?"--